BLOOD INDICES OF AFRICAN CATFISH (CLARIAS GARIEPINUS) FOLLOWING DIETARY ADMINISTRATION OF TALINUM TRIANGULARE - Tiamiyu, A. M; Olatoye, I. O; Adedeji, O. B (International Journal of Research -GRANTHAALAYAH, 2019)
The effects of Talinum triangulare on the haematological indices of Clarias gariepinus was investigated. T. triangulare leaf powder at 0, 0.5, 1.0, and 3.0% concentrations were fed to Clarias gariepinus juveniles (n=84; 117.3 ± 1.57 g; 26.70 ± 0.26 cm) as feed additive for a period of six (6) weeks. The packed cell volume (PCV) and Haemoglobin (Hb) concentration values, 34.67 ± 0.67%, 12.03 ± 0.26g/dl, respectively observed in the group fed with 1.0% were significantly higher (P<0.05) compare with the control group. Red blood cell counts (RBCs), white blood cell counts (WBCs), lymphocytes, MCV, MCH and MCHC recorded were marginally different (P>0.05) among the groups, were within standard for Clarias gariepinus, therefore adjudged not to indicate a negative physiological effect on the experimental fish. Blood indices values observed revealed that the varying additive levels of T. triangulare used had no negative physiological stress on the health status of the fish studied and haematological values observed were seen to be best in the group fed 1.0% T. triangulare. It could be recommended that 10g/kg of Talinum triangulare leaf powder be included in the diet of Clarias gariepinus for boosting of the animal blood and treatment of disease conditions such as anaemia.